1295. Susceptibility to Ceftolozane/Tazobactam and Comparators Among Pseudomonas aeruginosa Isolates Collected from Patients in Hospitals in Latin America – SMART 2017-2019. (4th December 2021) - Lob, Sibylle; Hackel, Meredith; Andrew DeRyke, C; Pavía, Jacquleine; Siddiqui, Fakhar; Young, Katherine; Motyl, Mary; Sahm, Daniel F
Abstract: Background: Ceftolozane is a cephalosporin specifically developed to have enhanced antibacterial activity against P. aeruginosa . Combined with tazobactam, it was approved by FDA and EMA for complicated urinary tract and intraabdominal infections, as well as hospital-acquired/ventilator-associated bacterial pneumonia. We evaluated the activity of ceftolozane/tazobactam (C/T) against P. aeruginosa isolates collected as part of the global SMART surveillance program in 10 countries in Latin America. Methods: In 2017-2019, 41 clinical labs each collected up to 250 consecutive gram-negative pathogens per year from various infection sources. A total of 21, 864 isolates were collected, of which 3, 335 (15.3%) were P. aeruginosa . MICs were determined using CLSI broth microdilution and breakpoints. C/T-nonsusceptible (NS) P. aeruginosa isolates were screened for genes encoding β-lactamases. Results: The table shows the antimicrobial susceptibility of P. aeruginosa and β-lactam-NS subsets. C/T was active against 85.9% of all collected P. aeruginosa, with lowest activity against isolates collected in Chile and Venezuela, where 28.0% and 23.2% of isolates, respectively, carried carbapenemases, and highest activity against isolates from Ecuador and Guatemala, where 2.2% and 4.2%, respectively, were carbapenemase-positive. Substantial variability in the activity of C/T and comparators was observed among β-lactam-NS subsets. In aggregate, however, C/T remained active against 59.9% of all meropenem-NS P. aeruginosa isolates from Latin America (n=1, 101), 57.3% of piperacillin/tazobactam-NS isolates (n=1054), 48.9% of cefepime-NS isolates (n=895), and 50.3% of ceftazidime-NS isolates (n=937). Conversely, other common β-lactams (meropenem, cefepime, ceftazidime, and piperacillin/tazobactam) remained active against 8-38% of these resistant isolates. Results Table Conclusion: C/T showed the highest activity against P. aeruginosa among the tested β-lactam antibiotics. While amikacin showed similar or better activity in vitro, its toxicities severely limit its clinical use. Given the desirability of β-lactams among clinicians, C/T represents an important option in the treatment of infections caused by P. aeruginosa in Latin America. Disclosures: Sibylle Lob, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Meredith Hackel, PhD MPH, IHMA (Employee)Pfizer, Inc. (Independent Contractor) C. Andrew DeRyke, PharmD, Merck & Co., Inc. (Employee, Shareholder) Jacquleine Pavía, MSc, Merck & Co, Inc (Employee) Fakhar Siddiqui, PhD, Merck & Co, Inc (Employee) Katherine Young, MS, Merck (Employee) Mary Motyl, PhD, Merck & Co., Inc. (Employee, Shareholder) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor)